2009
DOI: 10.1021/ic900134f
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Activation by “Non-nucleophilic” Lead Alkoxides

Abstract: A series of terminal lead alkoxides have been synthesized utilizing the bulky beta-diketiminate ligand [{N(2,6-(i)Pr(2)C(6)H(3))C(Me)}(2)CH](-) (BDI). The nucleophilicities of these alkoxides have been examined, and unexpected trends were observed. For instance, (BDI)PbOR reacts with methyl iodide only under forcing conditions yet reacts readily, but reversibly, with carbon dioxide. The degree of reversibility is strongly dependent upon minor changes in the R group. For instance, when R = isopropyl, the revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 21 publications
2
61
1
Order By: Relevance
“…In contrast to what is observed for (BDI)-tin-and lead-alkoxides [3,19], no reversion back to amide 2 or anilide 3 is observed, even under reduced pressure.…”
Section: Reactivity Of Tin-amide Complexescontrasting
confidence: 89%
See 1 more Smart Citation
“…In contrast to what is observed for (BDI)-tin-and lead-alkoxides [3,19], no reversion back to amide 2 or anilide 3 is observed, even under reduced pressure.…”
Section: Reactivity Of Tin-amide Complexescontrasting
confidence: 89%
“…Divalent b-diketiminate group 14 complexes have been the subject of several recent studies, including the synthesis and reactivity of germanium and tin hydrides [1,2], synthesis and reactivity of lead alkoxides [3,4], and the generation of unusual molecules such as a tin hydroxide stabilized by Fe(CO) 4 [5], and germanium and lead phosphides [6,7]. By far the most common b-diketiminate ligand used is [{N(2,6-i Pr 2 C 6 H 3 )C(Me)} 2 CH] À , or BDI.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations on structural features in lead(II) complexes were until about 10 years ago restricted to multidentate ligands, [1][2] and stable twoor three-coordinate lead(II) complexes were scarce. More recently, the utilisation of ubiquitous β-diketiminates has enabled the groups of Fulton [3][4][5][6][7][8][9][10][11] and a few others [12][13][14][15] to obtain a variety of three-coordinate lead(II) complexes (e.g. halides, amides and anilides, alkoxides and aryloxides, alkyls, phosphides), and our understanding of the reactivity of these species has improved accordingly.…”
Section: Aminofluoroalkoxide Amido and Boryloxo Lead(ii) Complexes † ‡mentioning
confidence: 99%
“…16 We have also shown that [Pb II ]boryloxides could be obtained as the two-coordinate [Pb(OB{CH(SiMe3)2}2)2] or as the three-coordinate [{2-Me2NCH2C6H4}PbOB{CH(SiMe3)2}2] bearing a bidentate organoligand. 17 Yet, beyond β-diketiminates [3][4][5][6][7][8][9][10][11][12][13][14][15] and bulky terphenyls, [18][19][20] the number of ligands suited to the design of heteroleptic low coordinate lead(II) complexes remains limited. [21][22][23][24][25] In particular, the implementation of potentially bidentate alkoxides for the preparation of soluble heteroleptic lead(II) species only includes a handful of examples, 16,24,26 even if homoleptic [Pb(OR)2]n and [Pb(μ2-OR)N(SiMe3)2]2 alkoxides have been known for some time.…”
Section: Aminofluoroalkoxide Amido and Boryloxo Lead(ii) Complexes † ‡mentioning
confidence: 99%
“…(Jana et al, 2011). A variety of terminal aryloxides , alkoxides (Tam et al, 2009), phosphides (Yao et al, 2007;Tam et al, 2012), amides and anilides (Harris et al, 2014) and alkyl (Jana et al, 2009;Taylor et al, 2015) (Tam et al, 2015). The role of mononuclear chloro complexes, in particular as precursors for salt metathesis reactions, was prominent in these studies.…”
Section: Introductionmentioning
confidence: 99%